High‐Loading Co Single Atoms and Clusters Active Sites toward Enhanced Electrocatalysis of Oxygen Reduction Reaction for High‐Performance Zn–Air Battery. (18th November 2022) - Zhang, Mengtian; Li, Hao; Chen, Junxiang; Ma, Fei‐Xiang; Zhen, Liang; Wen, Zhenhai; Xu, Cheng‐Yan
Abstract: The development of precious‐metal alternative electrocatalysts for oxygen reduction reaction (ORR) is highly desired for a variety of fuel cells, and single atom catalysts (SACs) have been envisaged to be the promising choice. However, there remains challenges in the synthesis of high metal loading SACs (>5 wt.%), thus limiting their electrocatalytic performance. Herein, a facile self‐sacrificing template strategy is developed for fabricating Co single atoms along with Co atomic clusters co‐anchored on porous‐rich nitrogen‐doped graphene (Co SAs/AC@NG), which is implemented by the pyrolysis of dicyandiamide with the formation of layered g‐C3 N4 as sacrificed templates, providing rich anchoring sites to achieve high Co loading up to 14.0 wt.% in Co SAs/AC@NG. Experiments combined with density functional theory calculations reveal that the co‐existence of Co single atoms and clusters with underlying nitrogen doped carbon in the optimized Co40 SAs/AC@NG synergistically contributes to the enhanced electrocatalysis for ORR, which outperforms the state‐of‐the‐art Pt/C catalysts with presenting a high half‐wave potential ( E 1/2  = 0.890 V) and robust long‐term stability. Moreover, the Co40 SAs/AC@NG presents excellent performance in Zn–air battery with a high‐peak power density (221 mW cm −2 ) and strong cycling stability, demonstrating great potential for energy storage applications. Abstract : High‐loading Co single atoms and Co atomic clusters co‐anchored on porous‐rich nitrogen‐doped graphene (Co SAs/AC@NG) is constructed via a facile self‐sacrificing template strategy. The Co40 SAs/AC@NG catalyst demonstrates remarkable performance with a half‐wave potential of 0.890 V for oxygen reduction reaction and a large power density of 221 mW cm −2 toward Zn–air battery.